Acute Kidney Injury following Acute Gastroenteritis at a Tertiary Care Center - Shah, Surendra Prasad; Poudel, Saurav; Parajuli, Bivusha; KC, Rupak; Gupta, Jitendra Prasad; Sah, Sandip (Journal of Nobel Medical College, 2026)
Background: Acute kidney injury is a significant and potentially reversible cause of morbidity and mortality, particularly in developing countries where pre-renal etiologies predominate. Acute gastroenteritis is a frequent precipitating illness due to dehydration and electrolyte imbalance. This study aimed to evaluate the clinical profile, biochemical parameters, etiological factors, and outcomes of AKI following acute gastroenteritis in a tertiary care hospital in eastern Nepal. Materials and Methods: A descriptive cross-sectional study was conducted at Nobel Medical College Teaching Hospital, Biratnagar, over one year among 71 patients aged ≥18 years who developed AKI in association with acute gastroenteritis. Data on demographics, clinical presentation, laboratory findings, and outcomes were collected and analysed using IBM SPSS Statistics version 29. AKI was diagnosed and staged according to KDIGO 2012 criteria. Descriptive statistics were used, and results were expressed as mean ± SD and percentage. Results: The mean age of patients was 51.4 ± 17.2 years, with a male predominance (59.2%). Moderate to severe dehydration was present in 87.3% of cases. Mean serum creatinine and urea were 4.6 ± 1.8 mg/dL and 130.5 ± 54.2 mg/dL, respectively. Hyponatremia (30.99%), hyperkalemia (25.35%), and metabolic acidosis (52.11%) were common abnormalities. KDIGO Stage 1 AKI occurred in 39.44%, Stage 2 in 32.39%, and Stage 3 in 28.17%. Infectious gastroenteritis was the leading cause (73.24%), and 87.32% achieved complete recovery. Conclusion: Acute kidney injury following acute gastroenteritis is a common clinical condition with a favorable prognosis. Dehydration and infectious etiology are the predominant contributing factors, and the majority of patients achieve complete renal recovery.